Evaluation of apocynin in vitro on high glucose-induced oxidative stress on tenocytes - Kurosawa, T. (Bone Joint Res, 2020)
AIMS: The purpose of this study was to evaluate the in vitro effects of apocynin, an inhibitor of nicotinamide adenine dinucleotide phosphate oxidase (NOX) and a downregulator of intracellular reactive oxygen species (ROS), on high glucose-induced oxidative stress on tenocytes. METHODS: Tenocytes from normal Sprague-Dawley rats were cultured in both control and high-glucose conditions. Apocynin was added at cell seeding, dividing the tenocytes into four groups: the control group; regular glucose with apocynin (RG apo+); high glucose with apocynin (HG apo+); and high glucose without apocynin (HG apo–). Reactive oxygen species production, cell proliferation, apoptosis and messenger RNA (mRNA) expression of NOX1 and 4, and interleukin-6 (IL-6) were determined in vitro. RESULTS: Expression of NOX1, NOX4, and IL-6 mRNA in the HG groups was significantly higher compared with that in the RG groups, and NOX1, NOX4, and IL-6 mRNA expression in the HG apo+ group was significantly lower compared with that in the HG apo– group. Cell proliferation in the RG apo+ group was significantly higher than in the control group and was also significantly higher in the HG apo+ group than in the HG apo– group. Both the ROS accumulation and the amounts of apoptotic cells in the HG groups were greater than those in the RG groups and were significantly less in the HG apo+ group than in the HG apo– group. CONCLUSION: Apocynin reduced ROS production and cell death via NOX inhibition in high-glucose conditions. Apocynin is therefore a potential prodrug in the treatment of diabetic tendinopathy. Cite this article: Bone Joint Res 2020;9(1):23–28.